Jurisdictional Analysis of Diversion for Children Accusing the Crime of Child Rape: Case Study Number 45/Pid.sus-Child/2022/PN Mdn - Shintauli Sihombing; Andry Syafrizal Tanjung (International Journal of Law and Society, 2024)
Children are a valuable treasure for parents. This is proven when married couples or parents who do not or have not had offspring or children then they try to find or get them even though they spend a lot of possessions. Likewise with the country. Both developed and developing countries really need children as the nation's successors. As world civilization continues to develop, parents are increasingly unwilling to give birth or have children for various reasons.The research specifications used in this research are analytical descriptive, that is, trying to describe or describe events and occurrences without carrying out hypotheses and statistical calculations. The data obtained will be presented systematically, the data required in this research is secondary data and primary data. This research is descriptive analysis, descriptive analysis, namely research aims to describe in detail, systematically and comprehensively everything related to this research problem and also normative juridically, namely research based on Ministerial regulations, books, along with analyzing Decision Number 45 /Pid.Sus-Anak/2022/Pn Mdn. Law Number 11 of 2012 concerning the Juvenile Justice System has the most basic substance in this law, namely the strict regulation of Restorative Justice and Diversion which is intended to keep children away from the justice process and avoid stigmatization of children who are in conflict with the law and are expected to can return to the social environment naturally. Factors that cause children to become perpetrators of criminal acts of sexual intercourse are due to causes in the form of environmental factors, faith factors, Social and Cultural Factors in the form of social and cultural factors can also influence children's views on sexuality and violence. Criminal acts committed by children must normatively seek diversion while still paying attention to the diversion requirements as regulated in Article 7 of the Juvenile Criminal Justice System Law. However, from the cases studied by the author, based on the District Court Decision, namely Decision Number 45/Pid.Sus-Anak/2022/Pn Mdn, the case does not meet the legal requirements for diversion even though the perpetrator is a child.